Evangelicals incorporated books and the business of religion in America - Vaca, Daniel 1980- (Cambridge, Massachusetts London, England Harvard University Press, 2019)
Finding profit : the ascendance of commercialism -- Brands of distinction: fundamentalist networks and the value of ecumenism -- Trade associating: evangelical allegiance in the mass market -- Righteous retail : women, family, and the social power of selling -- Financial faith: corporate finance and traditions of free enterprise -- The spirit of segmentation: niche markets and the pursuit of diversity.
"Long before evangelical Christians became known as a powerful political constituency, evangelicals were a profitable consumer constituency. In Evangelicals Incorporated Daniel Vaca argues that evangelical Christianity became a prominent form of religious life in the twentieth-century United States through commercial activity. To tell this story, Vaca focuses especially on the evangelical book industry, which not only has produced some of the bestselling titles in American history but also has inspired the world's largest secular media conglomerates to pursue evangelical markets. Drawing on corporate archives, personal letters, interviews, and more, [this work] explains how for-profit evangelical publishers and booksellers grew from modest roots to one of the most lucrative corners of the international book trade. By exploring areas of commercialism such as branding, retailing, marketing, and finance, Vaca illustrates how commercial media companies have cultivated and capitalized upon the expansive idea of evangelicalism since the end of the nineteenth century"--
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Christian-owned business enterprises -- United States; Evangelicalism -- Economic aspects -- United States; Christianity -- Economic aspects -- United States; Christian Literature -- Publishing -- United States; Church and mass media -- United States